A classification system and treatment algorithm for mastectomy flap ischemia in alloplastic breast reconstruction. Issue 10 (October 2020) - Koonce, Stephanie L.; Sarik, Jonathan R.; Forleiter, Craig M.; Newman, Martin I.
Summary: Background: Mastectomy flap necrosis remains a major cause of failed breast reconstruction with an associated significant financial/psychological burden. Language describing ischemic mastectomy flaps is imprecise as ischemia can result from many causes and can manifest in different ways. Similarly, management of mastectomy flap ischemia varies depending on its etiology. Intraoperative near-infrared imaging (NIR) with indocyanine green (ICG) is an established modality for evaluation of mastectomy flap perfusion. Herein, we define the types of flap ischemia demonstrated via NIR imaging and propose an algorithm for its management. Method: A retrospective review was performed of patients who underwent mastectomy and NIR imaging of mastectomy flaps from 2014 to 2017. Patient characteristics, operative details, and outcomes were recorded. Following retrospective review, distinct patterns of ischemia were identified, and a classification system and treatment algorithm were developed. Result: Type A; diffuse hypoperfusion can be caused by a number of factors (hypotension, vasoconstrictive agents, etc.). It is best treated with delayed reconstruction. Type B; geographic hypoperfusion may be caused by electro-cautery burn, inaccurate dissection, or retractor injury. It can be treated by resection/primary closure or delayed reconstruction. Type C; marginal/incisional hypoperfusion is best treated with debridement. Type D; diffuse marginal perfusion is seen with overfilled tissue-expanders or an oversized implant within a smaller skin envelope. Management includes deflation/downsizing. An algorithm was developed for treatment of the four ischemia types. Conclusion: NIR imaging aides in delineating the type of ischemic injury. Classification of mastectomy flap ischemia allows precise communication between providers and provides a framework for decision-making.